Evaluating political signals: The nature of bureaucratic response in minority preference purchasing - Terman, Jessica (2014)
The bureaucratic response literature has focused on the quantity and timing of agency outputs in response to political signals. This focus on quantity rather than more qualitative measures such as the content and character of response has made it difficult to fully understand the causes and conditions under which response occurs in relation to a given signal. In the context of minority preference purchasing policy in the State of Florida, this study examines the relationship between political signals and the content and character of bureaucratic response-what is referred to here as the nature of bureaucratic response. A theory is developed and supported through interview and archival data to suggest that bureaucratic actors evaluate signals and policymaker intentions in determining if and how to respond. The article also provides one of the first in-depth examinations of the inner workings of minority preference purchasing. - Reproduced.
Keywords: Purchasing